Dependence of Nanoparticles Synthesis Energy Consumption in the Gas Spark Discharge on Circuit Parameters - D.A. Mylnikov; A.A. Efimov; V.V. Ivanov (Журнал нано- та електронної фізики)
In this paper, we study the specific energy of titanium dioxide nanoparticles synthesis in a spark discharge in the air by varying the parameters of a discharge circuit. The dependence shows a maximum at a capacitor voltage of about 2 kV and a monotonic decrease with increasing voltage.